Sophisticated Deception in Junior Middle School Students: An ERP Study - Leng, Haizhou; Wang, Yanrong; Li, Qian; Yang, Lizhu; Sun, Yan (Frontiers in Psychology, 2019)
Sophisticated deception refers to the deception of others based on inferences of their mental states (e.g., answering honestly when inferring that the other will not believe their answer). Studying the brain mechanism of sophisticated deception in junior middle school students can provide physiological evidence for deception detection and deceptive ability measurement. Sixteen junior middle school students were asked to engage in different trial types (i.e., instructed truth/lie, chosen truth/lie), during which we recorded their response times (RT) along with electroencephalographic data to calculate event-related potentials (ERPs). We observed significant differences in amplitude [N2, P3, N450, and medial frontal negativity (MFN)] between chosen reactions (sophisticated deception, simple deception) and instructed reactions (instructed truth, instructed lie) in both the stimulus presentation and feedback stages. In the former, the task scores of participants in the chosen condition were significantly and positively correlated with the N2 amplitude over the central brain area during sophisticated deception. In the latter, the task scores of participants in the chosen condition were negatively correlated with the MFN amplitude over the left frontal and left frontocentral regions. Overall, deception intention, rather than simply making counterfactual statements, appears to underlie the increased demand for cognitive control in deceivers. This can be attributed to deceivers’ need to strongly consider their opponent’s mental state—the better the deceivers’ deceptive ability, the more they will make conjectures about the mental state of their opponent with sophisticated deception and monitor conflict; the less conflict they experience while answering honestly with the intention to deceive, the more conflict may arise when the results of their deception are inconsistent with these conjectures.